A dataset of floating debris accumulation at bridges after July 2021 flood in Germany and Belgium - Sébastien Erpicum; Daan Poppema; Lisa Burghardt; Loïc Benet; Davide Wüthrich; Elena-Maria Klopries; Benjamin Dewals (Scientific Data, 2024)
Abstract This paper presents a dataset documenting 71 floating debris accumulations at bridges following an extreme hydrological event that hit Belgium and Germany in July 2021. Data were collected from various sources including public authorities’ documents, public online databases, post event pictures and field visits. The dataset covers bridges geometry, flood conditions and debris accumulation. In particular, it systematically details accumulations dimensions and quantifies accumulations components, which contain a significant portion of anthropogenic objects, in addition to driftwood. This dataset constitutes a unique set of invaluable data to better understand debris accumulation at bridges but also to analyze their impact on both the affected structures and flood conditions.